Awareness of clean and healthy lifestyles among Amanah Kahmi Playground students' parents and staff. - Rusdiana Rusdiana (Talenta Publisher Universitas Sumatera Utara, 2025)
This activity provides education about clean and healthy living behavior to parents of students and teaching staff at the Amanah Kahmi Playground is one of the Community Service activities facilitated by the Universitas Sumatera Utara Community Service Institute unit, where this activity also wants to know the level of knowledge of parents of students in implementing healthy and clean living starting from home so that at school and also in the environment outside the home the child can apply clean and healthy living behavior. A clean and healthy lifestyle is the best solution as an early anticipation of the prevention of various transmissions of various diseases both from bacteria and viral transmission. The method used is a descriptive qualitative approach with techniques for providing counseling by giving questionnaires before counseling takes place. Researchers tabulated the results of the collected questionnaires and then collected data by scoring the questionnaires. The results of the questionnaires collected showed that the parents of students who filled out the questionnaire with a score of 9-8 were 4 people, with 7-6 were 14 people, filling out the questionnaire with a score of 5-4 were 8 people, so we can conclude that the level of knowledge of parents of students at Amanah Kahmi Playground is a moderate level of knowledge and with the education that has been provided should be able to increase knowledge and understanding of the function of clean and healthy living so that the application of these behaviors has been based from home.